DIAGNOSIS OF LUMBAR VERTEBRAL CANAL OBSTRUCTIVE PROCESSES: REVIEW OF LITERATURE - Khusanov Zafar Toshmurodovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Narrowing of the spinal canal is a major societal concern, as patients with this condition are among the most challenging cases in neurosurgery, often facing significant disability. Spinal canal stenosis is any condition that causes the canal to narrow and compress nerve structures at any point [1,3]. This can result from various spinal disorders, including degenerative diseases like spondylosis, arthritis, degenerative and spondylolytic spondylolisthesis, intervertebral disc herniations, or combinations of these issues.The study evaluates the effectiveness and relevance of different radiological techniques used to diagnose stenosis in the lumbar spine. It highlights the advantages and disadvantages of each method for detecting spinal canal stenosis.